The Use of ICT in Teaching Kiswahili Play in Secondary Schools in Uasingishu County, Kenya - Chepkemoi, Naumi; Wanyonyi, David (European Scientific Journal, ESJ, 2017)
The main aim of this study was to investigate the use of ICT in teaching Kiswahili plays in secondary schools as a way of cultivating interest and positive attitude towards drama at an early age. The objectives of the study were: To ascertain whether teachers of Kiswahili play have ICT skills for teaching Kiswahili plays and to examine attitude of teachers of Kiswahili towards integration of ICT in teaching Kiswahili plays The study used social learning theory by Bandura and the functionalism theory by John Dewey. The study employed a descriptive survey design to answer the research questions. Stratified sampling was used to categorize schools in to boys, girls, mixed schools, day and boarding schools. Simple random sampling was applied to select 275 students from a total of 918 students. The study used focus group discussion, questionnaires for teachers and students to collect data and interviews to provide further information on the teacher’s attitude on the use of ICT in teaching Kiswahili play and observation. The study showed limited use of ICT in teaching and learning of Kiswahili play and it adds up into the pool of existing knowledge and is beneficial to teachers since it gives suggestion on the best combination to motivate and arouse interest of teaching and also to the teacher training institutions in preparing teachers to adequately use ICT in instruction in classroom level and also to the curriculum developers.